2018
DOI: 10.1002/pen.25018
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Nanocomposite Membranes of Sulfonated Poly(Styrene‐Isobutylene‐Styrene) With Sulfonated Graphene Oxide for Fuel Cell and Protective Clothing Applications

Abstract: Graphene oxide (GO) and its sulfonated analog (sGO) have been incorporated into sulfonated poly(styrene‐isobutylene‐styrene) (SO3H SIBS) in order to enhance its water retention and proton conductivity, while aiming to block permeant passage through the material. The polymer nanocomposite membranes (PNMs) were tested for two applications: direct methanol fuel cell and chemical and biological protective clothing. The transport properties of the membranes were determined as a function of SIBS sulfonation level (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 62 publications
(166 reference statements)
0
6
0
Order By: Relevance
“…The membranes with better performance were SIBS 9‐g‐HexImCl ( α G = 49.8), SIBS‐g‐ButImCl ( α G = 49.4), and SIBS 17‐g‐HexImCl ( α G = 30.7). Comparing these values with previous modifications of SIBS such as grafting of poly(vinyl phosphonic acid) ( α G = 6.98), 33 incorporation of sulfonated carbon nanotubes ( α G = 7.39), 51 and sulfonated graphene oxide (~23) 55 ; it can be observed that there is a notable improvement in membrane selectivity with grafting of ionic liquid moieties, indicating superior potential over the former for CPC.…”
Section: Resultsmentioning
confidence: 66%
“…The membranes with better performance were SIBS 9‐g‐HexImCl ( α G = 49.8), SIBS‐g‐ButImCl ( α G = 49.4), and SIBS 17‐g‐HexImCl ( α G = 30.7). Comparing these values with previous modifications of SIBS such as grafting of poly(vinyl phosphonic acid) ( α G = 6.98), 33 incorporation of sulfonated carbon nanotubes ( α G = 7.39), 51 and sulfonated graphene oxide (~23) 55 ; it can be observed that there is a notable improvement in membrane selectivity with grafting of ionic liquid moieties, indicating superior potential over the former for CPC.…”
Section: Resultsmentioning
confidence: 66%
“…This situation may be like that reported by Ruiz-Col on et al ( 2019), where sulfonated SIBS was functionalized by adding sulfonated graphene oxide at various levels. 52 In their work, methanol permeability was independent of water absorption capabilities and IEC. It was argued that water transport was different from methanol transport.…”
Section: Transport Propertiesmentioning
confidence: 94%
“…To improve the water retention and proton conductivity of sulfonated poly(styrene‐isobutylene styrene) and to prevent permeant passage through the material, graphene oxide (GO) and its sulfonated analog (sGO) have been added. This material is used in chemical and biological protective clothing [260] …”
Section: Applications In High‐performance Textilesmentioning
confidence: 99%